Electromechanical coupling characteristics of double-layer piezoelectric quasicrystal actuators. (15th April 2021) - Huang, Yunzhi; Chen, Jian; Zhao, Min; Feng, Miaolin
Highlights: Quasicrystal materials are firstly incorporated in the MEMS/NEMS actuator-based devices. State vector method is extended to the electromechanical analysis of quasicrystals. Both Van der Waals and Casimir forces enlarge stress and deflection of quasicrystal actuators. The nonlocal scale parameter reduces displacement components in the phonon and phason fields. Static responses increase with the increment of the phonon-phason coupling elastic coefficient. Abstract: Electromechanical coupling characteristics of double-layer piezoelectric quasicrystal micro/nano-actuator are investigated by considering the effects of nanoscale interactions and nonlocal scale. The analytical models in the phonon, phason, and electric fields are derived via state vector formulation and propagator matrix method based on quasicrystal nonlocal elasticity theory. Governing equations of the models with geometrical nonlinearity are solved using the secant method. All nonlinear effects of the electrostatic force, van der Waals force, Casimir force, and nonlocal parameters on the mechanical behaviors of quasicrystal actuators are studied. Our results show that the increment of van der Waals force and Casimir force enlarges phonon stress and displacement. When the initial gap is larger than 3.72 nm, the effect of van der Waals force is more significant than that of Casimir force. The phonon-phason coupling elastic coefficient and the nonlocal scale parameter respectively have positive and negative effects on the static responses. Besides, the influence of the Casimir force on mechanical behavior depends on the volume ratio and scale of the quasicrystal nano-actuator. Graphical abstract: Electromechanical coupling characteristics of double-layer micro/nano-actuator made of quasicrystals are firstly investigated by considering the nonlinear effects of nanoscale interactions and nonlocal scale. Our results show that the distributed forces and the nonlocal scale parameter respectively have positive and negative effects on the static responses. The influence of the initial gap and phason fields on mechanical behaviors are also analyzed Image, graphical abstract .